2003
DOI: 10.1116/1.1579012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adsorbates on charge exchange in Li+ ion scattering from Ni(100)

Abstract: Resonant charge transfer during the backscattering of 3.0 keV Li ϩ from hydrogen-and iodine-covered Ni͑100͒ is probed with time-of-flight spectroscopy. Hydrogen adsorption on Ni͑100͒ induces only a small increase of the surface work function and the neutralization probabilities for backscattered Li are not significantly affected. Iodine adsorbs with some net negative charge, so that a dipole directed into the surface is expected. Such a dipole would increase the work function thereby decreasing the neutralizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Conversely, when the adsorbate is less electronegative, a negative workfunction change arises from a donation of charge from the adsorbate to the surface. However, this general trend is not always kept, and different exceptions have been reported in the literature. In particular, the systems considered here do not obey that common rule, and the interpretation must be done taking into account both the electronegativities and the polarizabilities of the adatoms …”
Section: Resultsmentioning
confidence: 86%
“…Conversely, when the adsorbate is less electronegative, a negative workfunction change arises from a donation of charge from the adsorbate to the surface. However, this general trend is not always kept, and different exceptions have been reported in the literature. In particular, the systems considered here do not obey that common rule, and the interpretation must be done taking into account both the electronegativities and the polarizabilities of the adatoms …”
Section: Resultsmentioning
confidence: 86%
“…Other authors have found systems in which similar irregularities can be observed. Thus, the adsorption of I to Ni(100) or Pt (111) has been reported as inducing charge transfer from the surface to the adsorbate and decreasing the work function by around 1 eV. Migani et al reported that the work function change induced by the presence of an adsorbed halide can be either positive or negative, depending on the surface metal .…”
Section: Introductionmentioning
confidence: 99%
“…Ni has a high work function of 5.2 eV, similar to that for Pd, and Al has a lower work function of 4.3 eV. Previous studies reported [ 21 , 22 ] that the work function of Ni is unaffected by hydrogen annealing. Thermo-transport measurements of hydrogen in metals showed that the hydrogen concentration in Ni was smaller than one-hundredth of those in Pd and Ti.…”
Section: Introductionmentioning
confidence: 62%